Study of COD Removal Rate on a Sequencing Batch Reactor (SBR) Treating Tapioca Wastewater - Happy Mulyani; Gregorius Prima Indra Budianto; Margono Margono; Mujtahid Kaavessina (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Industrial wastewater treatment using Sequencing Batch Reactor (SBR) can improve effluent quality at lower cost than that obtained by other biological treatment methods. Further optimization is still required to enhance effluent quality until it meets standard quality and to reduce the operating cost of treatment of high strength organic wastewater. The purpose of this research was to determine the effect of pretreatment (pH adjustment and prechlorination) and aeration time on effluent quality and COD removal rate in tapioca wastewater treatment using SBR. Pretreatment was done by (1) adjustment of tapioca wastewater pH to control (4.92), 7, and 8, and (2) tapioca wastewater prechlorination at pH 8 during hour using calcium hypochlorite in variation dosages 0, 2, 4, 6 mg/L Cl2, SBR operation was conducted according to following steps: (1) Filling of pre-treated wastewater into a bioreactor during 1 hour, and (2) aeration of the mixture of tapioca wastewater and activated sludge during 8 hours. Effluent sample was collected at every 2-hours aeration for COD analysis. COD removal rate mathematical formula was got by first deriving the best fit function between aeration time and COD. Optimum aeration time resulting in no COD removal rate. The value of COD effluent and its removal rate in optimum aeration time was used to determine the recommended of operation condition of pretreatment. Research result shows that chosen pH operation condition is pH 8. Prechorination can make effluent quality which meets standard quality and highest COD removal rate. The chosen Cl2 dosage is 6 mg/L.